2016
DOI: 10.1155/2016/9160540
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Mast Cell Specific Gangliosides Stimulates the Release of Newly Formed Lipid Mediators and Newly Synthesized Cytokines

Abstract: Mast cells are immunoregulatory cells that participate in inflammatory processes. Cross-linking mast cell specific GD1b derived gangliosides by mAbAA4 results in partial activation of mast cells without the release of preformed mediators. The present study examines the release of newly formed and newly synthesized mediators following ganglioside cross-linking. Cross-linking the gangliosides with mAbAA4 released the newly formed lipid mediators, prostaglandins D2 and E2, without release of leukotrienes B4 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Also, stimulation through receptors other than FcεRI can result in selective mediator release. For example, activation of Toll-like receptors (TLR) [17,54] or ganglioside cross-linking [55,56] on the mast cell surface leads to cytokine production and release in the absence of degranulation. Furthermore, chemokines do not induce mast cell degranulation, but they are able to induce the secretion of newly-synthesized mediators [57].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Also, stimulation through receptors other than FcεRI can result in selective mediator release. For example, activation of Toll-like receptors (TLR) [17,54] or ganglioside cross-linking [55,56] on the mast cell surface leads to cytokine production and release in the absence of degranulation. Furthermore, chemokines do not induce mast cell degranulation, but they are able to induce the secretion of newly-synthesized mediators [57].…”
Section: Plos Onementioning
confidence: 99%
“…The binding of many of these ligands such as SCF (stem cell factor), CCL3 (CC-chemokine ligand 3) and PAMPs (pathogenassociated molecular patterns) results in selective mediator release without degranulation [63]. Furthermore, cross-linking GD1b derived gangliosides on the surface of RBL-2H3 cells causes the release of newly formed and newly synthesized mediators without degranulation [55].…”
Section: Plos Onementioning
confidence: 99%
“…Also, rodent MCs express α-galactosyl derivatives of the ganglioside GD1b (90). Antibodies recognizing this ganglioside inhibit degranulation and histamine release by modulating FcεRI endocytosis (90, 91) but in contrast, are also able to promote release of cytokines and lipid mediators (92).…”
Section: Membrane Lipid Organizing Enzymes Are Targets To Modulate Mamentioning
confidence: 99%
“…It has also been shown that elevated expression levels of GM3, GM2, GM1 and GD1a can be observed during maturation of the human mast cell line HMC-1 [44] and that exogenous GM3 inhibits interleukin (IL)-3-stimulated cell proliferation of bone marrow-derived mouse mast cells [45]. In addition, it has been reported that cross-linking of GD1b-derived gangliosides activates RBL-2H3, a rat mast cell line, leading to the release of inflammatory cytokines, such as IL-4, IL-6 and TNFα [46].…”
Section: Inflammatory Cells and Gangliosidesmentioning
confidence: 99%